Dental Treatment Approach in Cantho University of Medicine and Pharmacy of Vietnam - Nguyen, Minh T; Truong, Nhan B; Nguyen, Thoa C (UI Scholars Hub, 2015)
The traditional morphological concept to dental care has shown many drawbacks and is not appropriate in many cases. To counteract these shortcomings, a problem-solving approach has been introduced in dental curriculum of Cantho University of Medicine and Pharmacy (CTUMP), Vietnam. This approach should be reflected in dental practice in CTUMP. Objective: To investigate the problem-solving approach to dental care of CTUMP by patterns of tooth extraction, and tooth rehabilitation. Methods: Cross-sectional data on DMF, dental treatments planned, dental treatments delivered from 1549 dental records of patients aged ≥18 of CTUMP were analyzed. Results: The majority of patients were aged 18-29 (929, 60%), classified as professional and skilled workers (1112 subjects, 72%), lived in urban areas (1156 subjects, 75%), and women (932, 60%). The number of teeth eventually receiving dental treatment was lower than the number of teeth indicated for the treatment. On average, each patient had 2 teeth receiving treatment. Tooth restoration was the most common treatment (1390, 70%). Molars were the most treated teeth (842, 43%). Molars showed statistically significant higher chance for restoration and extraction than premolars and anterior teeth (Wilcoxon-signed-ranks test p ≤ 0.017). No statistically significance was found in tooth replacement between premolar and molar regions. The dental treatments aimed to preserve all teeth regardless of dental regions. Tooth replacement may tend to be morphologically based rather than functionally as most prostheses restored the complete dental arch. Conclusions: The approach to dental care in CTUMP tends to be morphologically conservative.